Co-Branding Strategy in Increasing Consumer Trust: Food Industry Perspective - Gunawan (Yayasan Pendidikan Belajar Berdikari, 2023)
This study aims to analyze co-branding strategies as a marketing approach to enhance consumer trust in food industry products. Co-branding is a collaboration between two or more brands intended to create added value through the synergy of each party’s reputation and quality. In the highly competitive food industry, where perceptions of quality and product safety are critical, co-branding is believed to be an effective strategy for strengthening consumer trust. This research employs a qualitative approach using a descriptive method. The results indicate that co-branding strategies in the food industry have proven effective in increasing consumer trust. Collaborations between well-known brands can generate positive perceptions of products, expand market reach, and enhance consumer appeal. Case examples such as Chitato x Indomie and Oreo x Supreme demonstrate that co-branding not only boosts purchase interest but also builds consumer loyalty toward the collaborative products